183 Survival role of lymphadenectomy in patients surgically treated for apparent early-stage epithelial ovarian cancer. (13th November 2020) - Lembo, A; Dri, M; Longo, M; Oltolina, N; Riva, M; Artuso, V; Ghezzi, F; Casarin, J
Abstract : Objective: To evaluate the impact of lymphadenectomy (LND) on oncological outcomes in patients surgically treated for apparent early-stage epithelial ovarian cancer (aEOC). Methods: Consecutive patients with aEOC who underwent surgery at Del Ponte Hospital, (Varese-Italy) between January 2000 and December 2019 were analyzed. The cases were stratified according with the performance of lymphadenectomy (LND) or not (NO-LND). Demographic, pathologic and surgical-related characteristics were compared. Survivals curves were estimated with Kaplan-Meier methods and predictors of recurrence were investigated. Results: Overall 109 patients were included, 71 and 38 in LND and NO-LND groups, respectively. No differences were found in terms of baseline characteristics. Patients in LND group (vs. NO-LND) were less likely to present with high grade serous histotype (16, 22.9% vs.12, 44.4%, p<0.001), while mucinous and endometrioid histology represented 4, 5.7% vs. 6, 22.2% (p<0.001) and 36, 51.4% vs. 0, 0% (p<0.001), respectively. The G3 grade was more represented in LND group (40, 36.7% vs. 22, 20.2%, p<0.001). No differences in terms of FIGO stage (p=0.42), rate of minimally-invasive approach (63, 88.7% vs. 32, 84.2%, p=0.55), DFS (log-rank=0.79) and OS (log-rank=0.8) were found. With a median follow-up of 63.76 months, 13 patients (11.9%) recurred. LND was not found to be protective for relapse (p=0.77). However, among LND patients, the presence of lymph node metastasis (6/71, 8.4%) was significantly associated with recurrence (p= 0.01). Conclusion: The execution of systematic lymphadenectomy for aEOC staging did not influence survival outcomes. The presence of lymph node metastasis remained the main adverse prognostic factor associated with recurrence.